Prediction of Al2O3 leaching recovery in the Bayer process using statistical multilinear regresion analysis - Đurić I.; Đorđević P.; Mihajlović I.; Nikolić Đ.; Živković Ž. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper presents the results of defining the mathematical model which describes the dependence of leaching degree of Al2O3 in bauxite from the most influential input parameters in industrial conditions of conducting the leaching process in the Bayer technology of alumina production. Mathematical model is defined using the stepwise MLRA method, with R2 = 0.764 and significant statistical reliability - VIF<2 and p<0.05, on the one-year statistical sample. Validation of the acquired model was performed using the data from the following year, collected from the process conducted under industrial conditions, rendering the same statistical reliability, with R2 = 0.759.